Moderate Educational Curriculum and Its Impact on Forming University Student Personality Moderate Psychologically and Socially | المنهج “الوسطي التربوي” وأثره في تكوين شخصية الطالب الجامعي المعتدلة نفسياً ومجتمعياً - Adnan Mustafa (Al-Zahra : Journal for Islamic and Arabic Studies, 2015)
The study aimed to indicate the role of moderate approach "educational" in the psychological composition of the student campus and community interactions and reduce manifestations of extremism in the university environment. The study found the most important the following results: a moderateapproach educational organization of moderate Islam in a clear way that came out of Islam in Muslim personal breeding and the Muslim community on the truths of religion and its concepts and guidance comprehensive, integrated and balanced education to achieve happiness in this world and the hereafter. And it supports the construction of educational curriculum average student university on Islamic foundations in the perception of the existence and to the community and to the human spirit and the knowledge, and the curriculum is a university student who receives an educational curriculum that shape the character centrist Muslim university student formulation of social determinants. And it works to activate the average educational curriculum to reduce the manifestations of extremism in the university environment, and then local